(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Endometriosis is a disease where a tissue similar to the lining of the uterus implants and grows in other parts of the body, ovary, fallopian tubes, bladder, bowel etc. Objective: The aim of this treatment was to see how Ayurvedic treatment can help in endometriosis by reducing pain, improving flow in periods, regression of cyst size and supporting overall life quality. To present a case of endometriosis managed successfully with Ayurvedic medicines, Panchkarma therapies and diet, lifestyle modifications. Ayurveda describes that Ama pachan, Vatanulomana, Dosha samya, Panchkarma, restoring Agni and Rasayan, Vajikaran are some approaches that can help to treat Endometriosis. Methods: A single case of 31-year-old female diagnosed with endometriosis with severe dysmenorrhea was documented. Detailed case history, physical examination and lab tests were noted. Ayurvedic treatment plan was designed as per classical principles including Ayurvedic oral medicines and Vasti karma. Classical formulations targeting Vata-Kapha dosha were selected. The treatment protocol was administered over 12 months and patient was regularly assessed for all her symptoms every month. Results: After 1 month of treatment, patient reported marked reduction in period pain intensity and after 6-8 weeks, pelvic and back pain also reduced. Menstrual flow normalized after 4 months with no post menstrual spotting per vaginum. After 4, 6 and 12-months ultrasound showed progressive regression in endometriotic lesion size along with significant reduction of symptoms. General health parameters like energy levels, quality of sleep, exercise capacity improved reflecting better life quality. Conclusion: Ayurvedic management can provide symptomatic relief, regression in cyst size and inflammation and improve quality of life in endometriosis by addressing the Dosha imbalances rather than suppression of merely symptoms. Findings suggest that Ayurvedic treatment offers safe and holistic approach to the management of endometriosis with reduced recurrence.